2021
DOI: 10.3390/nu13124507
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis Strain Plasma Intake Suppresses the Incidence of Dengue Fever-like Symptoms in Healthy Malaysians: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Dengue fever (DF) is a mosquito-borne disease still with no effective treatment or vaccine available. A randomized, placebo-controlled, double-blinded, parallel-group trial was undertaken to evaluate the efficacy of oral intake of Lactococcus lactis strain plasma (LC-Plasma) on the presentation and severity of DF-like symptoms among healthy volunteers. Study participants (320) were assigned into two groups, and consumed either placebo or LC-Plasma tablets (approximately 100 billion cells/day) for 8 weeks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As a result, the humoral and cellular immune responses were enhanced, and EcN biofilm increased the frequencies of systemic memory and IgA + B cells ( 109 , 110 ). Likewise, the Lactococcus lactis strain decreased severity and symptoms in volunteers with Dengue fever (DF) compared to the placebo group, promoted IFN-γ and TGF-β cytokines secretion, and reduced serum IgE and IL-4 cytokine levels in mice models ( 111 , 112 ). Bacillus toyonensis ( B .…”
Section: The Effects Of Probiotics On Vaccine Efficacymentioning
confidence: 99%
“…As a result, the humoral and cellular immune responses were enhanced, and EcN biofilm increased the frequencies of systemic memory and IgA + B cells ( 109 , 110 ). Likewise, the Lactococcus lactis strain decreased severity and symptoms in volunteers with Dengue fever (DF) compared to the placebo group, promoted IFN-γ and TGF-β cytokines secretion, and reduced serum IgE and IL-4 cytokine levels in mice models ( 111 , 112 ). Bacillus toyonensis ( B .…”
Section: The Effects Of Probiotics On Vaccine Efficacymentioning
confidence: 99%
“…Specifically, it increased secretory IgA levels in saliva and maintained the activation level of pDC with CD86 positive ( 33 ). Finally, it was reported that LC-Plasma significantly attenuated Dengue fever-like symptoms in Malaysian healthy adult volunteers ( 34 ) and significantly reduced the cumulative school absent days by infectious disease in Vietnam elementary school children ( 35 ). Figure 1 shows the overview of the immunomodulatory effect and the antiviral mechanism of LC-Plasma.…”
Section: Probiotic Research Against Infectious Disease In Pre-covid-1...mentioning
confidence: 99%